Development of an OpenCV Solution for Recognition and Analysis of Plant GrowthProcesses in a Digital Learning Module - Rinaldy Juan Sutyono (2019)
On the use-case of the experiment of plant growth analysis, which is a part of Smart Classroom’s project, the growth process of a plant will be analysed by tracking its height regularly. The purpose of this thesis is to develop a prototype implementation, that serves to analyse the growth process of a plant by using image processing. This thesis includes the analysis of the method for object localization and the development of an OpenCV based Prototype for analyzing plant growth.